Impact of right ventricular size and function on survival following transcatheter aortic valve replacement - Ito, Saki; Pislaru, Sorin V.; Soo, Wern Miin; Huang, Runqing; Greason, Kevin L.; Mathew, Verghese; Sandhu, Gurpreet S.; Eleid, Mackram F.; Suri, Rakesh M.; Oh, Jae K.; Nkomo, Vuyisile T. (International journal of cardiology, 2016)
The impact of pre-procedural RV size and function on outcomes following transcatheter aortic valve replacement (TAVR) is not well established. The aim of this study was to investigate the role of right ventricular size and function on outcomes following TAVR. Between November 2008 and June 2013, 268 consecutive patients (age 80.5±7.9years, aortic valve area 0.79±0.16cm2) with symptomatic severe aortic stenosis (AS) undergoing TAVR at Mayo Clinic were included. Transthoracic echocardiographic quantitative and semiquantitative assessment of RV chamber size and systolic function was performed and included tricuspid annular plane systolic excursion (TAPSE), RV systolic excursion velocity (S′), fractional area change (FAC), RV index of myocardial performance (RIMP). The primary endpoint of all-cause mortality after TAVR was measured and observed in 65 patients (median follow up duration: 412days). Univariate analysis identified semiquantitative RV dilatation (p<0.001) and systolic dysfunction (p=0.013), RV basal dimension (p=0.003) and RV outflow proximal dimension (p=0.031) to be of prognostic significance. After multivariate adjustment, patients with semiquantitative RV dilatation (HR 2.61, 95% CI 1.45–4.65, p=0.002) and larger RV basal dimension (HR 1.07, 95% CI per mm 1.02–1.11, p=0.007) had significantly worse survival even after adjusting for age, sex, Society of Thoracic Surgeons (STS) risk score, left ventricular ejection fraction, tricuspid regurgitation, pulmonary artery systolic pressure, and atrial fibrillation. RV dilatation is an important determinant of postoperative outcomes in patients undergoing TAVR.